Bivalve mollusc culture research in Thailand. - McCoy, EW and Chongpeepien, Tanittha, eds. (Manila, Philippines ICLARM, 1988)
ICLARM Technical Reports 19
Keywords: Mollusc culture; Mollusc; Bivalve culture